Multikulturalisme Dalam Perspektif Islam - Putri, Anjellie Dasviana; Ritonga, Nurhayani; Anwar, Kasful; A, Ansori (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Islamic views regarding multicultural education as well as Islamic responses to diversity in society, particularly in educational institutions, as an attempt to ensure that every ethnic group obtains equal rights. Multicultural education is a crucial basis in maintaining unity and social integration in diverse environments, by educating the public on the importance of equality, justice, diversity, unity, race, ethnicity, language, tradition, as well as respect for religious beliefs, peace and harmony. This Multicultural Education is in line with the principles of Islamic teachings, which are found in the Quran which emphasizes the importance of appreciating diversity. The implementation of multiculturalism in community life can be done in a variety of ways, ranging from mutual appreciation of differences and building effective communication, as well as developing the empathy of each individual towards the other. Additionally, the development of multiculturalism education and developing inclusive policies could be undertaken. With these things then the implementation of multiculturalism in community life can help build harmonious and mutually respectful relationships among individuals despite having different backgrounds.